GAMBARAN KECEPATAN BERJALAN PADA LANSI DI VILLA BALARAJA - Ria Puspita Dewi (2021)
Background: The elderly are called the elderly, which is a term for people who are 60 years old or more and are physiologically experiencing a process of decreasing body functions. Habitual strolling pace predicts many scientific situations in later life, however decreases with age. Gait is the result of integration between bones, nervous system (central and peripheral nervous system), muscles, and environmental factors (shoes, stepping surface). Objective: The motive of this look at is to decide whether or not there may be a dating among on foot velocity and git sample with the aged in Balaraja Villa. Methods: In this examine the approach used is descriptive correlational studies layout is cross sectional. Measuring instrument: Walking speed will be measured by stride length and walking time. Keywords : Walking speed, Elderly, Gait parameter